Cooperative Learning: Another Way to Learn Together - D'olivares Durán, Nelson (Universidad Pedagógica y Tecnológica de Colombia, 2014)
AbstractThe purpose of this article is to provide an overview about cooperative learning as another way of learning together in the English classes. Also, as a qualitative study (action participative research), it focused on learning by means of the practice in terms of exploring how cooperative learning helps improve the English speaking skill of students in their English classes, showing it as one more way for raising students’ interest in English learning in a scholarly environment.Key words: cooperative learning, work in small groups, speaking skill.